Laboratory evaluation of Mesocyclops annulatus (Wierzejski, 1892) (Copepoda: Cyclopidea) as a predator of container-breeding mosquitoes in Argentina - Micieli, María Victoria (2002)
In laboratory bioassays we tested the predatory capacity of the copepod Mesocyclops annulatus on Aedes aegypti and Culex pipiens larvae. A single adult female of M. annulatus caused 51.6% and 52.3% mortality of 50 first instar larvae of Ae. aegypti and Cx. pipiens respectively, in a 72 h test period. When alternative food was added to the containers, mortality rates declined to 16% and 10.3% for Ae. aegypti and Cx. pipiens respectively. When 50 first instar larvae of each of the two mosquito species tested were placed together with a single adult female of M. annulatus, mortality rates were 75.5% for Ae. aegypti larvae and 23.5% for Cx. pipiens larvae in a three day test period. Different density of adult females of M. annulatus ranged from 5 to 25 females produced mortality rates of Ae. aegypti first instar larvae from 50% to 100% respectively. When a single adult female of M. annulatus was exposed to an increasing number of first-instar Ae. aegypti larvae ranging from 10 to 100, 100% mortality was recorded from 1 to 25 larvae, then mortality declined to 30% with 100 larvae. The average larvae killed per 24 h period by a single copepod were 29.